A kind of attapulgite-based hydrogel and preparation method thereof

By modifying the concave and convex rod soil and introducing branched acrylate quaternary ammonium salts to form a uniformly dispersed crosslinking structure, the problem of insufficient water retention and mechanical properties of traditional hydrogels in low humidity environments is solved, and efficient moisture retention and mechanical strength improvement are achieved.

CN119463070BActive Publication Date: 2025-04-04GANSU AGRI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510066358.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-04
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

Traditional hydrogels have poor water retention properties in low humidity environments and have low mechanical properties, which are prone to rupture or deformation, limiting their application in complex environments.

Method used

By introducing modified concave and convex rod soil, branched acrylate quaternary ammonium salt is used to modify concave and convex rod soil, expand its layer spacing and enhance the interface bonding force with the organic matrix to form a uniformly dispersed crosslinking structure.

Benefits of technology

It significantly improves the water absorption, water retention and mechanical properties of the hydrogel, and can maintain moisture for a long time in drought or low-humidity environments, extend service life, and improve functional reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of hydrogels, and in particular to an attapulgite-based hydrogel and a preparation method thereof. The hydrogel is prepared by polymerization of an olefin monomer and modified attapulgite, wherein the modified attapulgite is obtained by modifying attapulgite with a branched acrylate quaternary ammonium salt. The hydrogel exhibits excellent water absorption, water retention and mechanical properties. Its water absorption rate is as high as 292%, and it has excellent water retention capacity in a low-humidity environment. It can retain moisture for a long time in a drought or low-humidity environment, significantly improving the continuous water supply capacity, and is suitable for the fields of agriculture, soil improvement and ecological restoration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogels, and in particular to an attapulgite-based hydrogel and a preparation method thereof. Background Art

[0002] Hydrogel is a polymer material with a three-dimensional network structure. Due to its excellent water absorption and water retention, it has been widely used in agriculture, soil improvement, ecological restoration and other fields. Hydrogel can absorb a large amount of water and slowly release water in a dry environment, thereby providing continuous water support for plant growth. However, traditional hydrogels have poor water retention in low-humidity environments, and the water evaporates quickly, making it difficult to meet the long-term water supply needs in drought or low-humidity environments. In addition, traditional hydrogels have low mechanical properties and are easily broken or deformed by external forces during use, resulting in a shortened service life and limiting their application in complex environments. Therefore, how to improve the water retention and mechanical properties of hydrogels has become a focus of researchers.

[0003] In order to solve these problems, researchers have tried to introduce inorganic materials into hydrogels to improve their overall performance. Attapulgite is a natural layered silicate mineral with a large specific surface area, excellent adsorption properties and good thermal stability. Introducing attapulgite into hydrogels can significantly improve the water absorption and water retention of hydrogels, while enhancing their structural stability. However, unmodified attapulgite has poor dispersibility in hydrogels and is prone to form agglomerates in the matrix, resulting in insufficient binding force with the organic matrix and inability to fully exert its performance advantages. In addition, the poor interfacial compatibility of unmodified attapulgite with the hydrogel matrix may result in the failure to significantly improve the mechanical properties and structural uniformity of the hydrogel. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a attapulgite-based hydrogel and a preparation method thereof, so as to improve the water absorption, water retention and mechanical properties of the attapulgite-based hydrogel to meet practical application requirements.

[0005] Based on the above purpose, the present invention provides a attapulgite hydrogel, which is obtained by polymerizing 35.1-55.3 parts of olefinic monomers and 8-12 parts of modified attapulgite, by weight.

[0006] Furthermore, the vinyl monomer comprises, by weight, 20-30 parts of acrylic acid, 0.1-0.3 g of N,N'-methylenebisacrylamide and 15-25 parts of acrylamide.

[0007] Further, the preparation method of the modified attapulgite is as follows:

[0008] (1) Under a nitrogen atmosphere, diethanolamine and pentaerythritol tetraacrylate are added to methanol, stirred at room temperature for 20-28 hours, distilled under reduced pressure, and purified by chromatography to obtain a branched polyol containing a tertiary amine;

[0009] (2) adding a branched polyol containing a tertiary amine and isocyanoethyl methacrylate into dichloromethane, stirring at room temperature for 10-14 hours, and then transferring into n-hexane to precipitate an oily substance, separating it, washing it with n-hexane, and rotary evaporating it to obtain a branched acrylate containing a tertiary amine;

[0010] (3) Under nitrogen protection, add the branched acrylate containing tertiary amine and hydroquinone into dichloromethane, stir for 20-40 minutes, then add benzyl chloride dropwise, raise the temperature to 40-50°C, stir and reflux for 20-28 hours, cool and crystallize, wash with ether, and vacuum dry to obtain a branched acrylate quaternary ammonium salt;

[0011] (4) Add branched acrylate quaternary ammonium salt and acrylamide to a mixed solution of deionized water and anhydrous ethanol, stir for 20-40 minutes, then add attapulgite, raise the temperature to 70-80°C, stir and reflux for 5-7 hours, reduce the pressure and filter, wash with water, wash with ethanol, and vacuum dry to obtain modified attapulgite.

[0012] Preferably, in step (1), the weight ratio of diethanolamine, pentaerythritol tetraacrylate and dichloromethane is 1.4-4.2:1-3:5-20.

[0013] Preferably, the eluent used for the chromatography purification in step (1) is a mixture of ethyl acetate and petroleum ether in a volume ratio of 1:50.

[0014] Preferably, in step (2), the weight ratio of the branched polyol containing tertiary amine, isocyanoethyl methacrylate and dichloromethane is 2-4:3.5-6.5:5-20.

[0015] Preferably, in step (3), the weight ratio of the branched acrylate containing tertiary amine, hydroquinone, dichloromethane and benzyl chloride is 2-4:0.5-1.5:5-10:0.5-1.5.

[0016] Preferably, in step (4), the weight ratio of the branched acrylate quaternary ammonium salt, acrylamide, deionized water, anhydrous ethanol and attapulgite is 1.5-2.5:3-5:100-150:100-150:8-12.

[0017] Preferably, the specific surface area of ​​the attapulgite in step (4) is 100-200m 2 / g.

[0018] Furthermore, the present invention provides a method for preparing a attapulgite hydrogel, comprising the following steps: under a nitrogen atmosphere, adding modified attapulgite to deionized water, stirring for 20-40 minutes, heating to 65-75°C, adding ammonium persulfate, stirring for 20-40 minutes, then adding acrylic acid, N,N'-methylenebisacrylamide and acrylamide, continuing to stir for 2-4 hours, washing with water, washing with ethanol, vacuum drying, grinding and sieving to obtain a attapulgite-based hydrogel.

[0019] Preferably, the amount of deionized water added is 30 times the weight of the modified attapulgite.

[0020] Preferably, the amount of ammonium persulfate added is 0.1 times the weight of the modified attapulgite.

[0021] Beneficial effects of the present invention:

[0022] The present invention provides a attapulgite-based hydrogel and a preparation method thereof. The hydrogel exhibits excellent swelling properties, and its water absorption rate can reach 292%. It has excellent water retention in a low-humidity environment, and can retain moisture for a long time in a drought or low-humidity environment, effectively improving the continuous water supply capacity of the hydrogel. This characteristic makes it have a wide range of application potentials in the fields of agriculture, soil improvement and ecological restoration, and is particularly suitable for water management and plant growth support in arid areas.

[0023] The attapulgite-based hydrogel provided by the present invention has high tensile and compressive properties, and exhibits good mechanical strength and structural stability. During use, the hydrogel is not easy to break or deform, can withstand mechanical stress and environmental fluctuations, significantly improves its service life and functional reliability, and meets multiple application requirements in complex environments. This excellent mechanical property comes from the optimized cross-linked structure and uniform dispersion of attapulgite.

[0024] The present invention modifies attapulgite by using branched acrylate quaternary ammonium salt, effectively expands the interlayer distance of attapulgite, and enhances the interfacial bonding force between attapulgite and organic matrix. The modified attapulgite can be more evenly dispersed in the hydrogel and participate in the construction of the cross-linked network, further improving the water absorption, water retention and mechanical properties of the hydrogel. Especially in a low humidity environment, its water retention capacity is significantly enhanced, providing reliable support for water resource management. DETAILED DESCRIPTION

[0025] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0026] The attapulgite in the specific embodiment of the present invention was purchased from Mingguang Tianke Mineral Co., Ltd., with a specific surface area of ​​150m 2 / g.

[0027] Example 1: (1) Under a nitrogen atmosphere, 1.4 g of diethanolamine and 1 g of pentaerythritol tetraacrylate were added to 5 g of methanol, stirred at room temperature for 20 h, distilled under reduced pressure, and purified by chromatography using ethyl acetate / petroleum ether (volume ratio of 1:50) as an eluent to obtain a branched polyol containing a tertiary amine;

[0028] (2) Add 2 g of branched polyol containing tertiary amine and 3.5 g of isocyanoethyl methacrylate to 5 g of dichloromethane, stir at room temperature for 10 h, and then transfer to 10 g of n-hexane to precipitate an oily substance, separate it, wash it with n-hexane, and rotary evaporate it to obtain a branched acrylate containing tertiary amine;

[0029] (3) Under nitrogen protection, add 2 g of branched acrylate containing tertiary amine and 0.5 g of hydroquinone into 5 g of dichloromethane, stir for 20 min, then add 0.5 g of benzyl chloride dropwise, heat to 40 °C, stir and reflux for 20 h, cool and crystallize, wash with ether, and dry in vacuum to obtain branched acrylate quaternary ammonium salt;

[0030] (4) Add 1.5 g of branched acrylate quaternary ammonium salt and 3 g of acrylamide to a mixed solution of 100 g of deionized water and 100 g of anhydrous ethanol, stir for 20 min, then add 8 g of attapulgite, heat to 70 ° C, stir and reflux for 5 h, filter under reduced pressure, wash with water, wash with ethanol, and vacuum dry to obtain modified attapulgite;

[0031] (5) Under a nitrogen atmosphere, 8 g of modified attapulgite was added to 250 g of deionized water, stirred for 20 min, heated to 65 °C, added with 0.8 g of ammonium persulfate, stirred for 20 min, then added with 20 g of acrylic acid, 0.1 g of N,N'-methylenebisacrylamide and 15 g of acrylamide, stirred for 2 h, washed with water, washed with ethanol, vacuum dried, and ground through a 80-mesh sieve to obtain attapulgite-based hydrogel.

[0032] Example 2: (1) Under a nitrogen atmosphere, 2.8 g of diethanolamine and 2 g of pentaerythritol tetraacrylate were added to 10 g of methanol, stirred at room temperature for 24 h, distilled under reduced pressure, and purified by chromatography using ethyl acetate / petroleum ether (volume ratio of 1:50) as an eluent to obtain a branched polyol containing a tertiary amine;

[0033] (2) Add 3 g of branched polyol containing tertiary amine and 5 g of isocyanoethyl methacrylate to 10 g of dichloromethane, stir at room temperature for 12 h, and then transfer to 20 g of n-hexane to precipitate an oily substance, separate it, wash it with n-hexane, and rotary evaporate it to obtain a branched acrylate containing tertiary amine;

[0034] (3) Under nitrogen protection, 3 g of branched acrylate containing tertiary amine and 1 g of hydroquinone were added to 8 g of dichloromethane, stirred for 30 min, and then 1 g of benzyl chloride was added dropwise. The temperature was raised to 45 °C, stirred and refluxed for 24 h, cooled and crystallized, washed with ether, and vacuum dried to obtain a branched acrylate quaternary ammonium salt;

[0035] (4) Add 2 g of branched acrylate quaternary ammonium salt and 4 g of acrylamide to a mixed solution of 120 g of deionized water and 120 g of anhydrous ethanol, stir for 30 min, then add 10 g of attapulgite, heat to 75 ° C, stir and reflux for 6 h, reduce pressure and filter, wash with water, wash with ethanol, and vacuum dry to obtain modified attapulgite;

[0036] (5) Under a nitrogen atmosphere, 10 g of modified attapulgite was added to 300 g of deionized water, stirred for 30 min, heated to 70 °C, added with 1 g of ammonium persulfate, stirred for 30 min, then added with 25 g of acrylic acid, 0.2 g of N,N'-methylenebisacrylamide and 20 g of acrylamide, stirred for 3 h, washed with water, washed with ethanol, vacuum dried, and ground through an 80-mesh sieve to obtain attapulgite-based hydrogel.

[0037] Example 3: (1) Under a nitrogen atmosphere, 4.2 g of diethanolamine and 3 g of pentaerythritol tetraacrylate were added to 20 g of methanol, stirred at room temperature for 28 h, distilled under reduced pressure, and purified by chromatography using ethyl acetate / petroleum ether (volume ratio of 1:50) as an eluent to obtain a branched polyol containing a tertiary amine;

[0038] (2) 4 g of a branched polyol containing a tertiary amine and 6.5 g of isocyanoethyl methacrylate were added to 20 g of dichloromethane, stirred at room temperature for 14 h, and then transferred to 40 g of n-hexane to precipitate an oily substance, which was separated, washed with n-hexane, and rotary evaporated to obtain a branched acrylate containing a tertiary amine;

[0039] (3) Under nitrogen protection, 4 g of branched acrylate containing tertiary amine and 1.5 g of hydroquinone were added to 10 g of dichloromethane, stirred for 40 min, and then 1.5 g of benzyl chloride was added dropwise. The temperature was raised to 50 ° C, stirred and refluxed for 28 h, cooled and crystallized, washed with ether, and vacuum dried to obtain a branched acrylate quaternary ammonium salt;

[0040] (4) Add 2.5 g of branched acrylate quaternary ammonium salt and 5 g of acrylamide to a mixed solution of 150 g of deionized water and 150 g of anhydrous ethanol, stir for 40 min, then add 12 g of attapulgite, heat to 80 ° C, stir and reflux for 7 h, filter under reduced pressure, wash with water, wash with ethanol, and dry in vacuum to obtain modified attapulgite;

[0041] (5) Under a nitrogen atmosphere, 12 g of modified attapulgite was added to 350 g of deionized water, stirred for 40 min, heated to 75 °C, 1.2 g of ammonium persulfate was added, stirred for 40 min, and then 30 g of acrylic acid, 0.3 g of N,N'-methylenebisacrylamide and 25 g of acrylamide were added. The mixture was stirred for 4 h, washed with water, washed with ethanol, vacuum dried, and ground through a 80-mesh sieve to obtain an attapulgite-based hydrogel.

[0042] Comparative Example 1:

[0043] The difference between Comparative Example 1 and Example 2 is that the branched acrylate quaternary ammonium salt in step (4) is replaced by a branched acrylate containing a tertiary amine;

[0044] The specific steps are as follows:

[0045] (1) Under nitrogen atmosphere, 2.8 g of diethanolamine and 2 g of pentaerythritol tetraacrylate were added to 10 g of methanol, stirred at room temperature for 24 h, distilled under reduced pressure, and purified by chromatography using ethyl acetate / petroleum ether (volume ratio of 1:50) as eluent to obtain a branched polyol containing tertiary amine;

[0046] (2) Add 3 g of branched polyol containing tertiary amine and 5 g of isocyanoethyl methacrylate to 10 g of dichloromethane, stir at room temperature for 12 h, and then transfer to 20 g of n-hexane to precipitate an oily substance, separate it, wash it with n-hexane, and rotary evaporate it to obtain a branched acrylate containing tertiary amine;

[0047] (3) Add 2 g of branched acrylate containing tertiary amine and 4 g of acrylamide to a mixed solution of 120 g of deionized water and 120 g of anhydrous ethanol, stir for 30 min, then add 10 g of attapulgite, heat to 75 ° C, stir and reflux for 6 h, filter under reduced pressure, wash with water, wash with ethanol, and vacuum dry to obtain modified attapulgite;

[0048] (4) Under a nitrogen atmosphere, 10 g of modified attapulgite was added to 300 g of deionized water, stirred for 30 min, heated to 70 °C, added with 1 g of ammonium persulfate, stirred for 30 min, then added with 25 g of acrylic acid, 0.2 g of N,N'-methylenebisacrylamide and 20 g of acrylamide, stirred for 3 h, washed with water, washed with ethanol, vacuum dried, and ground through an 80-mesh sieve to obtain attapulgite-based hydrogel.

[0049] Comparative Example 2:

[0050] The difference between Comparative Example 2 and Example 2 is that the branched acrylate containing tertiary amine in step (3) is replaced by a branched polyol containing tertiary amine;

[0051] The specific steps are as follows:

[0052] (1) Under nitrogen atmosphere, 2.8 g of diethanolamine and 2 g of pentaerythritol tetraacrylate were added to 10 g of methanol, stirred at room temperature for 24 h, distilled under reduced pressure, and purified by chromatography using ethyl acetate / petroleum ether (volume ratio of 1:50) as eluent to obtain a branched polyol containing tertiary amine;

[0053] (2) Under nitrogen protection, add 3 g of branched polyol containing tertiary amine and 1 g of hydroquinone into 8 g of dichloromethane, stir for 30 min, then add 1 g of benzyl chloride dropwise, heat to 45 °C, stir and reflux for 24 h, cool and crystallize, wash with ether, and dry in vacuum to obtain a branched quaternary ammonium salt;

[0054] (3) Add 2 g of branched quaternary ammonium salt and 4 g of acrylamide to a mixed solution of 120 g of deionized water and 120 g of anhydrous ethanol, stir for 30 min, then add 10 g of attapulgite, heat to 75 ° C, stir and reflux for 6 h, filter under reduced pressure, wash with water, wash with ethanol, and vacuum dry to obtain modified attapulgite;

[0055] (4) Under a nitrogen atmosphere, 10 g of modified attapulgite was added to 300 g of deionized water, stirred for 30 min, heated to 70 °C, added with 1 g of ammonium persulfate, stirred for 30 min, then added with 25 g of acrylic acid, 0.2 g of N,N'-methylenebisacrylamide and 20 g of acrylamide, stirred for 3 h, washed with water, washed with ethanol, vacuum dried, and ground through an 80-mesh sieve to obtain attapulgite-based hydrogel.

[0056] Comparative Example 3:

[0057] The difference between Comparative Example 3 and Example 2 is that the branched acrylate quaternary ammonium salt in step (4) is replaced by octadecyltrimethylammonium bromide;

[0058] The specific steps are as follows:

[0059] (1) Add 2 g of octadecyltrimethylammonium bromide and 4 g of acrylamide to a mixed solution of 120 g of deionized water and 120 g of anhydrous ethanol, stir for 30 min, then add 10 g of attapulgite, heat to 75 ° C, stir and reflux for 6 h, filter under reduced pressure, wash with water, wash with ethanol, and vacuum dry to obtain modified attapulgite;

[0060] (2) Under a nitrogen atmosphere, 10 g of modified attapulgite was added to 300 g of deionized water, stirred for 30 min, heated to 70 °C, 1 g of ammonium persulfate was added, stirred for 30 min, and then 25 g of acrylic acid, 0.2 g of N,N'-methylenebisacrylamide and 20 g of acrylamide were added. The mixture was stirred for 3 h, washed with water, washed with ethanol, vacuum dried, and ground through a 80-mesh sieve to obtain attapulgite-based hydrogel.

[0061] Comparative Example 4:

[0062] The difference between Comparative Example 4 and Example 2 is that: no acrylamide is added in step (4), and the amount of acrylamide added in step (5) is 24 g;

[0063] The specific steps are as follows:

[0064] (1) Under nitrogen atmosphere, 2.8 g of diethanolamine and 2 g of pentaerythritol tetraacrylate were added to 10 g of methanol, stirred at room temperature for 24 h, distilled under reduced pressure, and purified by chromatography using ethyl acetate / petroleum ether (volume ratio of 1:50) as eluent to obtain a branched polyol containing tertiary amine;

[0065] (2) Add 3 g of branched polyol containing tertiary amine and 5 g of isocyanoethyl methacrylate to 10 g of dichloromethane, stir at room temperature for 12 h, and then transfer to 20 g of n-hexane to precipitate an oily substance, separate it, wash it with n-hexane, and rotary evaporate it to obtain a branched acrylate containing tertiary amine;

[0066] (3) Under nitrogen protection, 3 g of branched acrylate containing tertiary amine and 1 g of hydroquinone were added to 8 g of dichloromethane, stirred for 30 min, and then 1 g of benzyl chloride was added dropwise. The temperature was raised to 45 °C, stirred and refluxed for 24 h, cooled and crystallized, washed with ether, and vacuum dried to obtain a branched acrylate quaternary ammonium salt;

[0067] (4) Add 2 g of branched acrylate quaternary ammonium salt to a mixed solution of 120 g of deionized water and 120 g of anhydrous ethanol, stir for 30 min, then add 10 g of attapulgite, heat to 75 ° C, stir and reflux for 6 h, filter under reduced pressure, wash with water, wash with ethanol, and vacuum dry to obtain modified attapulgite;

[0068] (5) Under a nitrogen atmosphere, 10 g of modified attapulgite was added to 300 g of deionized water, stirred for 30 min, heated to 70 °C, added with 1 g of ammonium persulfate, stirred for 30 min, then added with 25 g of acrylic acid, 0.2 g of N,N'-methylenebisacrylamide and 24 g of acrylamide, stirred for 3 h, washed with water, washed with ethanol, vacuum dried, and ground through a 80-mesh sieve to obtain attapulgite-based hydrogel.

[0069] Comparative Example 5:

[0070] The difference between Comparative Example 5 and Example 2 is that the modified attapulgite in step (5) is replaced by attapulgite;

[0071] The specific steps are as follows:

[0072] Under a nitrogen atmosphere, 10 g of attapulgite was added to 300 g of deionized water, stirred for 30 min, heated to 70 °C, 1 g of ammonium persulfate was added, stirred for 30 min, and then 25 g of acrylic acid, 0.2 g of N,N'-methylenebisacrylamide and 20 g of acrylamide were added, and stirring was continued for 3 h. The mixture was washed with water, washed with ethanol, vacuum dried, and ground through a 80-mesh sieve to obtain attapulgite-based hydrogel.

[0073] Performance Test:

[0074] Water absorption: The hydrogel was immersed in deionized water. The excess water on the surface of the hydrogel was taken out every 12 h and dried with filter paper and weighed until the mass of the hydrogel no longer changed significantly. At this time, the swelling equilibrium of the hydrogel was reached. The water absorption rate was calculated, and the water absorption rate = (mass of the hydrogel after water absorption equilibrium - initial mass of the hydrogel) / initial mass of the hydrogel. The results are shown in Table 1.

[0075] Water retention: The swollen equilibrium hydrogel samples were placed in a culture dish and placed in a constant temperature and humidity chamber with humidity of 20%, 40%, and 80% and temperature of 25 °C. After 24 hours, they were taken out and weighed. The water retention rate = (initial mass of hydrogel - mass of hydrogel after 24 hours) / initial mass of hydrogel. The results are shown in Table 1.

[0076] Compression performance: The hydrogel samples were prepared into cylinders with a radius of 15 mm and a height of 20 mm. The compression performance of the hydrogel samples was tested using a universal mechanical testing machine. The compression rate was 20 mm / min, the compression strain was 85%, and there were 5 parallel samples in each group. The results are shown in Table 1.

[0077] Stretchability: The hydrogel was made into a 5.0 cm × 1.0 cm × 0.5 cm strip and fixed between the two ends of the clamp with a spacing of 2.0 cm. The tensile properties of the hydrogel samples were tested using a universal mechanical testing machine at a stretching rate of 20 mm / min. The results are shown in Table 1.

[0078] Table 1 Performance test results

[0079]

[0080] Data Analysis:

[0081] From the data in Examples 1-3 in Table 1, it can be seen that the attapulgite-based hydrogel prepared by the present invention has high swelling performance, and the water absorption rate can reach 292%. Most importantly, it has excellent water retention in a low-humidity environment, which helps to retain moisture for a long time in arid or low-humidity environments, and improves the continuous water supply capacity of the hydrogel, thereby playing an important role in agriculture, soil improvement, and ecological restoration. In addition, the hydrogel also has high tensile and compressive properties, which indicates that the hydrogel is not easy to break or deform during use, especially under conditions where it needs to withstand mechanical stress or environmental fluctuations, which can effectively improve its service life and functional reliability, and meet multiple needs in practical applications.

[0082] It can be seen from the data of Example 2 and Comparative Example 1 in Table 1 that the use of benzyl chloride to modify the branched acrylate containing tertiary amine can effectively improve the water absorption and water retention of the attapulgite-based hydrogel, and the tensile and compressive properties of the hydrogel are improved. This is mainly because the branched acrylate containing tertiary amine modified by benzyl chloride has a quaternary ammonium salt group, which can be effectively intercalated between attapulgite layers, increasing the interlayer spacing while optimizing the cross-linking structure formed by the interlayer olefinic groups and the extralayer olefinic monomers.

[0083] It can be seen from the data of Example 2 and Comparative Example 2 in Table 1 that the alkenyl groups on the branched structure intercalated between the attapulgite can significantly improve the tensile and compressive properties of the hydrogel. This is mainly because the alkenyl groups on the branched structure can form crosslinks with the acrylamide between the layers and the alkenyl groups outside the layers, thereby improving the binding force between the attapulgite and the hydrogel and the dispersion of the attapulgite in the hydrogel.

[0084] It can be seen from the data of Example 2 and Comparative Example 3 in Table 1 that, compared with the conventional attapulgite modified by octadecyltrimethylammonium bromide intercalation, the attapulgite modified by the branched acrylate quaternary ammonium salt used in the present invention can significantly improve the water absorption, water retention, tensile and compression properties of the hydrogel. In particular, the water retention in a low humidity environment can be improved, which may be because the branched acrylate quaternary ammonium salt can further expand the interlayer spacing and the water retention capacity between the layers.

[0085] It can be seen from the data of Example 2 and Comparative Example 4 in Table 1 that, compared with the introduction of acrylamide in the later stage, the addition of part of acrylamide in the intercalation modification stage can effectively improve the tensile and compressive properties of the hydrogel. This may be because the addition of acrylamide in the intercalation modification stage can improve the dispersion of acrylamide between layers, thereby forming a hydrogel with uniform structure between the layers.

[0086] It can be seen from the data of Example 2 and Comparative Example 5 in Table 1 that, compared with directly adding attapulgite, the attapulgite-based hydrogel prepared by the present invention has higher water absorption, water retention, and significantly improved tensile and compressive properties. This is mainly due to the fact that the present invention modifies attapulgite by using branched acrylate quaternary ammonium salt, thereby expanding the interlayer spacing of attapulgite, while optimizing the interfacial bonding force between attapulgite and the hydrogel matrix, and significantly improving the dispersibility and crosslinking uniformity of attapulgite in the hydrogel. In addition, the modified attapulgite can more effectively participate in the construction of the hydrogel network, enhance the structural stability and mechanical strength of the hydrogel, thereby improving its overall performance and meeting the high performance requirements in practical applications.

[0087] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A attapulgite-based hydrogel, characterized in that: The invention is obtained by polymerizing 35.1-55.3 parts of olefinic monomer and 8-12 parts of modified attapulgite clay by weight; The olefinic monomer comprises, by weight: 20-30 parts of acrylic acid, 0.1-0.3 parts of N,N'-methylenebisacrylamide and 15-25 parts of acrylamide; The preparation method of the modified attapulgite is as follows: (1) Under a nitrogen atmosphere, diethanolamine and pentaerythritol tetraacrylate are added to methanol, stirred at room temperature for 20-28 hours, distilled under reduced pressure, and purified by chromatography to obtain a branched polyol containing a tertiary amine; (2) adding a branched polyol containing a tertiary amine and isocyanoethyl methacrylate into dichloromethane, stirring at room temperature for 10-14 hours, and then transferring into n-hexane to precipitate an oily substance, separating it, washing it with n-hexane, and rotary evaporating it to obtain a branched acrylate containing a tertiary amine; (3) Under nitrogen protection, add the branched acrylate containing tertiary amine and hydroquinone into dichloromethane, stir for 20-40 minutes, then add benzyl chloride dropwise, raise the temperature to 40-50°C, stir and reflux for 20-28 hours, cool and crystallize, wash with ether, and vacuum dry to obtain a branched acrylate quaternary ammonium salt; (4) adding branched acrylate quaternary ammonium salt and acrylamide to a mixed solution of deionized water and anhydrous ethanol, stirring for 20-40 minutes, then adding attapulgite, heating to 70-80°C, stirring and reflux reaction for 5-7 hours, filtering under reduced pressure, washing with water, washing with ethanol, and vacuum drying to obtain modified attapulgite; In the step (4), the weight ratio of the branched acrylate quaternary ammonium salt, acrylamide, deionized water, anhydrous ethanol and attapulgite is 1.5-2.5:3-5:100-150:100-150:8-12.

2. The attapulgite-based hydrogel according to claim 1, characterized in that: In the step (1), the weight ratio of diethanolamine, pentaerythritol tetraacrylate and methanol is 1.4-4.2:1-3:5-20.

3. The attapulgite-based hydrogel according to claim 1, characterized in that: The eluent used in the chromatography purification in step (1) is a mixture of ethyl acetate and petroleum ether in a volume ratio of 1:

50.

4. The attapulgite-based hydrogel according to claim 1, characterized in that: In the step (2), the weight ratio of the branched polyol containing tertiary amine, isocyanoethyl methacrylate and dichloromethane is 2-4:3.5-6.5:5-20.

5. The attapulgite-based hydrogel according to claim 1, characterized in that: In the step (3), the weight ratio of the branched acrylate containing tertiary amine, hydroquinone, dichloromethane and benzyl chloride is 2-4:0.5-1.5:5-10:0.5-1.

5.

6. The attapulgite-based hydrogel according to claim 1, characterized in that: The specific surface area of ​​the attapulgite in step (4) is 100-200m 2 / g.

7. A method for preparing the attapulgite-based hydrogel according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: adding modified attapulgite into deionized water under a nitrogen atmosphere, stirring for 20-40 minutes, heating to 65-75°C, adding ammonium persulfate, stirring for 20-40 minutes, adding acrylic acid, N,N'-methylenebisacrylamide and acrylamide, continuing stirring for 2-4 hours, washing with water, washing with ethanol, vacuum drying, grinding and sieving to obtain attapulgite-based hydrogel.

8. The method for preparing the attapulgite-based hydrogel according to claim 7, characterized in that: The amount of deionized water added is 30 times the weight of the modified attapulgite.

9. The method for preparing the attapulgite-based hydrogel according to claim 7, characterized in that: The amount of ammonium persulfate added is 0.1 times the weight of the modified attapulgite.

Citation Information

Patent Citations

  • Modified acrylic acid-based high-strength salt-tolerant high-absorptivity resin and preparation method thereof

    CN111087558A

  • Hardened polyurethane acrylate adhesive and preparation method thereof

    CN113817437A